Relationship between frequency of posyandu visits and nutritional status of toddlers in bug-bug village - aryani, made putu (Journal of Midwifery and Nursing, 2025)
In Indonesia, under-five nutrition problems, such as malnutrition and stunting, remain a major challenge, despite the implementation of various intervention programs, such as posyandu. Based on data from Indonesia's Potential Village (PODES) in 2021, about 90% of villages in Indonesia already have posyandu, there are 40% of toddlers visit posyandu every month, 32% of toddlers visit irregularly, and 28% of toddlers never visit posyandu. The purpose of this study was to identify the relationship between the frequency of maternal visits to posyandu and the nutritional status of toddlers. This study used quantitative methods with descriptive analysis and a cross-sectional approach. The sample of this study was 126 toddlers aged 1-3 years who were selected based on inclusion and exclusion criteria. The statistical test used was chi-square. The results revealed that most of the respondents, namely 81 people (66.9%), who regularly visited the posyandu had normal nutritional status. The statistical test results showed a p value of 0.01 which means there is a relationship between the frequency of visits to the posyandu with the nutritional status of toddlers in Bug-bug Village in 2023